2021
DOI: 10.1093/molbev/msab118
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Portrait of the Progenitor SARS-CoV-2 and Its Dominant Offshoots in COVID-19 Pandemic

Abstract: Global sequencing of hundreds of thousands of genomes of Severe acute respiratory syndrome coronavirus 2, SARS-CoV-2, has continued to reveal new genetic variants that are the key to unraveling its early evolutionary history and tracking its global spread over time. Here, we present the heretofore cryptic mutational history and spatiotemporal dynamics of SARS-CoV-2 from an analysis of thousands of high-quality genomes. We report the likely most recent common ancestor of SARS-CoV-2, reconstructed through a nove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 53 publications
3
65
0
Order By: Relevance
“…Evidence used to support this hypothesis comes from a comparative genomic analysis of more than 175,000 genomes, which delineated 22 distinct SARS-CoV-2 haplogroups with a broad geographic distribution within China, pointing towards an early emergence and widespread cryptic circulation of the virus well before its isolation in January 2020 [25]. Recently, Kumar et al reconstructed the mutational history of SARS-CoV-2 using a so called 'mutation order approach' (MOA) [26]. From their analysis of more than 174,000 genomes, major mutational fingerprints revealed that it is useful to identify and track the spatiotemporal evolution of novel coronavirus.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence used to support this hypothesis comes from a comparative genomic analysis of more than 175,000 genomes, which delineated 22 distinct SARS-CoV-2 haplogroups with a broad geographic distribution within China, pointing towards an early emergence and widespread cryptic circulation of the virus well before its isolation in January 2020 [25]. Recently, Kumar et al reconstructed the mutational history of SARS-CoV-2 using a so called 'mutation order approach' (MOA) [26]. From their analysis of more than 174,000 genomes, major mutational fingerprints revealed that it is useful to identify and track the spatiotemporal evolution of novel coronavirus.…”
Section: Discussionmentioning
confidence: 99%
“…On 30 January 2020, as recommended by its Emergency Committee, the WHO declared the outbreak ‘Public Health Emergency of International Concern’ and alerted countries to be prepared for the deployment of emergency measures such as containment, active surveillance and contact tracing. 1 However, by then, the virus had already been spreading worldwide 3 and by 27 February 2020, cases of COVID-19 had already been reported in 53 countries, prompting the WHO on 11 March to characterise the disease as a global pandemic. 1 …”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 positive routine samples from mid-December 2019 were also found in Italy 14 , France 43 and the United States 44 , suggesting the pathogen was circulating in small numbers by the end of 2019 outside of China, but resulting in excess mortality only from Spring 2020. Phylogenetic analysis 45 suggests that a progenitor of the SARS-CoV-2 variant first identified in Wuhan might have been spreading outside of China before the known beginning of the city’s outbreak.…”
Section: Discussionmentioning
confidence: 99%